Comparison of Health Belief Model Constructs Based on Birth Type among Primiparous Pregnant Women in Bandar Abbas, Iran - Sakineh Dadipoor; Teamur Aghamolaei; Ali Ramezankhani; Ali Safari-Moradabadi (Hamadan University of Medical Sciences, 2017)
Background and Objectives: Cesarean section is the most widespread birth-related surgery throughout the world, the mortality rate of which is seven times as high as that of vaginal delivery. The present study aimed to compare the Health Belief Model (HBM) constructs based on the selected birth type among the primiparous pregnant women in Bandar Abbas, Iran. Materials and Methods: This descriptive-analytical, cross-sectional study was carried out on 210 primiparous women referring to the health care centers of Bandar Abbas in 2016. The study population was performed using a combination of cluster and simple random sampling methods. The data were collected by means of a questionnaire consisting of three parts, namely demographic data, awareness, and HBM constructs. The data were analyzed in SPSS software (version 18) using descriptive statistics, Chi-square test, and one-way ANOVA. Results: The mean age of the participants was 24.56±4.96 years.Furthermore, 36.2% and 63.8% of the mothers had undergone cesarean section and normal delivery, respectively. The mean score of maternal awareness regarding the advantages and disadvantages of delivery methods was 6.63%. In addition, there was a significant statistical difference in all HBM constructs between the mothers of different delivery types (P<0.05). Conclusion: Based on the findings of the present study, the number of the unessential cesarean sections can be reduced by undertaking some measures. These actions include the consistent implementation of educational courses on the side effects and hazards of cesarean section by the health care centers as well as identification and removal of the barriers to mothers' choice of vaginal delivery with the aim of attracting the mothers' trust for undergoing this delivery.